Antiretroviral therapy among patients with HIV in Almaty, Kazakhstan: the implication for HIV-associated tuberculosis control - Alfiya Denebayeva; Arpine Abrahamyan; Aelita Sargsyan; Karine Kentenyants; Ainur Zhandybayeva; Zhamilya Nugmanova; Anarkhan Nurkerimova; Karapet Davtyan; Marat Tukeyev (Journal of Infection in Developing Countries)
Introduction: Antiretroviral therapy (ART) is an effective preventive strategy against tuberculosis (TB) in people living with HIV (PLWH). In Kazakhstan, according to the revised HIV treatment guideline (2017), ART should be initiated immediately after HIV diagnosis established, regardless of CD4+ count.